Navigating Federal Travel - Cox, E. (Berrett-Koehler Publishers, 2012)
Get the right directions for federal travel! Don't get lost in the tangled web of rules and regulations governing federal travel. Make sure you have the one guide that will put you on the road to being a knowledgeable and compliant government traveler-- Navigating Federal Travel: A Q & A Roadmap. This essential reference is geared not only to government travelers and those authorizing and approving travel, but also to those who provide travel management services to government agencies. The guide is organized in question-and-answer format, similar to the Federal Travel Regulation (FTR), and is presented to be readily accessible and informative. The information is based on the author's years of experience as a federal travel manager as well as the FTR, Government Accountability Office and Civilian Board of Contract Appeals decisions, and pertinent legislation and mandates. As a supplement to the FTR, the guide includes examples of actual and potential situations the traveler may encounter before, during, and after approval of authorized travel. The book offers clear and concise information on: " How to determine the need for travel " How travel is authorized and by whom " How the employee pays for expenses incurred in performing official travel " How the employee is reimbursed for authorized travel and travel-related expenses. Navigating Federal Travel also includes coverage of best practices for the Agency/Organization Program Coordinator (A/OPC), who is responsible for managing the government travel charge card program. Appendices offer helpful websites and resources as well as special information for relocation. Get the right directions and follow the rules with Navigating Federal Travel: A Q & A Roadmap